PENGARUH KECEMASAN TERHADAP MINAT BELAJAR MATEMATIKA SISWA - Lisma, Eryanti; Rahmadhani, Rahmadhani; Siregar, Machrani Adi Putri (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
Anxiety is a condition that arises when there is a threat of helplessness, feelings of isolation. Anxiety is also a matter of excessive concern and internalized as well as a variety of summative symptoms that cause significant disturbances in social or work functions that cause a decrease in interest in learning mathematics in students. Interest has a very important role in the learning process because interest is one of the determining factors in the success or action of the instructor's objectives to be achieved. Students who are not interested in the subject matter will show less sympathetic, lazy and not passionate attitudes. The data collection method uses a questionnaire for learning interest variables. The purpose of this study was to determine the relationship of student anxiety to interest in learning mathematics. The research subjects were 30 students. Based on the results of the study, it was concluded that: (1) there was a relationship of students 'anxiety to the interest in learning mathematics, or in other words the interest in learning mathematics at all was related by students' anxiety in their interest in learning mathematics in the face of examinations, especially in mathematics; (2) there is no relationship of interest in learning mathematics, or in other words there is no relationship of interest in learning mathematics that students have in learning mathematics. The relationship of anxiety that occurs between mathematics learning interest and anxiety is negative 0,417; (3) as a stimulus, anxiety about learning interest has a proven influence on the relationship of students' anxiety to mathematics learning interest